"Nietzsche, aesthetics and modernity" - "Rampley, Matthew" (New York, 2007)
Nietzsche, Aesthetics and Modernity analyses Nietzsche's response to the aesthetic tradition, tracing in particular the complex relationship between the work and thought of Nietzsche, Kant and Hegel. Focusing in particular on the critical role of negation and sublimity in Nietzsche's account of art, it explores his confrontation with modernity and his attempt to posit a revitalized artistic practice as the counter-movement to modern nihilism. Drawing on the full range of his published and unpublished writings, together with his comments on figures as diverse as Wagner, Zola, Delacroix and Laurence Sterne, it highlights the extent to which Nietzsche counters the culture of his own time with a dialectical notion of aesthetic interpretation and practice. As such, Nietzsche the dialectician articulates a position that proves to be intimately connected to the negative dialects of Theodor Adorno.
Keywords: "Nietzsche, friedrich Wilhelm,1844-1900-Aesthetics"